Pengaruh Disiplin Kerja dan Etos Kerja terhadap Produktifitas Kerja di PT. Intidragon Suryatama Mojokerto - Yulaidin, Totok (SENTRI: Jurnal Riset Ilmiah, 2025)
The increasingly tight industrial competition today, combined with global trade tensions, fluctuating import tariff policies, and rapid technological shifts, demands that manufacturing companies enhance their productivity to remain competitive. This study aims to analyze the influence of industrial culture on work productivity at the shoe manufacturing company PT. Intidragon Suryatama. In this research, industrial culture is examined through two key dimensions: employee work discipline and work ethic, both of which are considered essential behavioral foundations that shape overall organizational performance. A quantitative approach was employed using a survey method involving 100 employees selected from various production units within the company. Data were collected through a structured questionnaire and analyzed using multiple linear regression to determine the magnitude of the relationship between variables. The findings indicate that industrial culture has a significant and positive effect on employee productivity, demonstrating that disciplined behavior and a strong work ethic contribute directly to improved output and operational efficiency. These results underscore the importance of cultivating a structured, consistent, and value-driven work culture as a strategic asset in strengthening employee commitment and enhancing production performance. Furthermore, the study suggests that organizations should continuously reinforce cultural values through training, supervision, and managerial support to ensure sustainable productivity improvements amid rising industrial challenges.